Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12967-016-0921-x
|View full text |Cite|
|
Sign up to set email alerts
|

Guizhi-Shaoyao-Zhimu decoction attenuates rheumatoid arthritis partially by reversing inflammation-immune system imbalance

Abstract: BackgroundGuizhi-Shaoyao-Zhimu decoction (GSZD) has been extensively used for rheumatoid arthritis (RA) therapy. Marked therapeutic efficacy of GSZD acting on RA has been demonstrated in several long-term clinical trials without any significant side effects. However, its pharmacological mechanisms remain unclear due to a lack of appropriate scientific methodology.MethodsGSZD’s mechanisms of action were investigated using an integrative approach that combined drug target prediction, network analysis, and experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…Guizhi-Shaoyao-Zhimu Decoction is a representative prescribed formula to treat RA. A synthetic approach [19] that combined drug target prediction, network analysis, and experimental validation indicated that Guizhi-Shaoyao-Zhimu Decoction may partially attenuate RA by means of reversing inflammation-immune system disequilibrium and regulating the HDAC1-HSP90AA1-NFKB2-IKBKB-TNF-α signaling axis. As one of novel Chinese patent medicines, Xinfeng capsule shows benefits in alleviating joint pain, swelling, and early morning stiffness, and it could also ameliorate extra-articular manifestations such as anemia, platelet disorder, lipid metabolism disturbance, abnormal cardiopulmonary function, depression, and quality of life with few adverse reaction [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Guizhi-Shaoyao-Zhimu Decoction is a representative prescribed formula to treat RA. A synthetic approach [19] that combined drug target prediction, network analysis, and experimental validation indicated that Guizhi-Shaoyao-Zhimu Decoction may partially attenuate RA by means of reversing inflammation-immune system disequilibrium and regulating the HDAC1-HSP90AA1-NFKB2-IKBKB-TNF-α signaling axis. As one of novel Chinese patent medicines, Xinfeng capsule shows benefits in alleviating joint pain, swelling, and early morning stiffness, and it could also ameliorate extra-articular manifestations such as anemia, platelet disorder, lipid metabolism disturbance, abnormal cardiopulmonary function, depression, and quality of life with few adverse reaction [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine has great potential in the treatment of many in ammatory and immunoregulatory diseases [21,22]. Pulsatilla chinensis (Bunge) Regel, a traditional Chinese herb, has the functions of clearing away heat and detoxi cation, stopping dysentery and drying dampness, and has a good therapeutic effect on bacteria, virus infection and malignant tumors in clinic [23].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies indicate that Chinese herbal formulae achieve their particular therapeutic efficacy by modifying the imbalanced disease-associated network through the interactions of their active components and corresponding targets. Therefore, our research group has proposed a workflow that involves the integration of traditional Chinese medicine and network pharmacology, highlighting a "network target, multi-component therapeutics" paradigm to effectively reveal the modes of action of different Chinese herbal formulae [13][14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%